2021
DOI: 10.3758/s13423-021-01987-w
|View full text |Cite
|
Sign up to set email alerts
|

Emotion matters: Face ensemble perception is affected by emotional states

Abstract: Ensemble coding is the ability of the visual system to extract a summary statistic from a set of stimuli. For example, observers often spontaneously extract an average face identity from a set of faces. Ensemble coding is known to operate in the frame of a distributed/global attention model. Because both attention and holistic processing are modulated by emotionwhere positive emotions broaden the scope of attention and facilitate global processing, whereas negative emotions narrow the scope of attention and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Moreover, the current study investigated the assessment of two key dimensions of emotion: valence and intensity, rather than the global experience of group emotion (Peng et al, 2022). The results suggested that different processing mechanisms underlie the evaluation of valence and intensity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the current study investigated the assessment of two key dimensions of emotion: valence and intensity, rather than the global experience of group emotion (Peng et al, 2022). The results suggested that different processing mechanisms underlie the evaluation of valence and intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous studies on the effect of familiar faces on emotional perception focused on single faces, instead of faces within a group (Holland et al, 2021;Pino et al, 2019;Švegar et al, 2019). It is unclear whether this theory applies to group emotion processing as well.…”
mentioning
confidence: 99%